2004
DOI: 10.1074/jbc.m313745200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase-2Cα as a Positive Regulator of Insulin Sensitivity through Direct Activation of Phosphatidylinositol 3-Kinase in 3T3-L1 Adipocytes

Abstract: During differentiation, expression of protein phosphatase-2C␣ (PP2C␣) is increased in 3T3-L1 adipocytes.To elucidate the role of PP2C␣ in insulin signaling, we overexpressed wild-type (WT) PP2C␣ by adenovirus-mediated gene transfer in 3T3-L1 adipocytes. Overexpression of PP2C␣-WT enhanced the insulin sensitivity of glucose uptake without any changes in the early steps of insulin signaling. Infection with adenovirus 5 expressing PP2C␣-WT increased phosphatidylinositol 3-kinase (PI3K) activities in the immunopre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…Increased proliferation, differentiation and activation of PI3K in adipocytes results in greater insulin sensitivity. 8,37 Therefore, the ability of Ad-36 to induce adipogenesis may be important for influencing insulin sensitivity. Indeed, Ad-36 infection of rats increased by several fold adipose tissue expression of many adipogenic genes including PPARg and C/EBP-b, reduced fasting insulin levels to 54% and significantly improved the HOMA index.…”
Section: Discussionmentioning
confidence: 99%
“…Increased proliferation, differentiation and activation of PI3K in adipocytes results in greater insulin sensitivity. 8,37 Therefore, the ability of Ad-36 to induce adipogenesis may be important for influencing insulin sensitivity. Indeed, Ad-36 infection of rats increased by several fold adipose tissue expression of many adipogenic genes including PPARg and C/EBP-b, reduced fasting insulin levels to 54% and significantly improved the HOMA index.…”
Section: Discussionmentioning
confidence: 99%
“…Overactivation of Smad2 in Ppm1a-deficient Mice-Previous studies have shown that Ppm1a could modulate Smad and PI3K/Akt signaling pathways, both of which are involved in wound healing process and keratinocyte migration (9,12,19,21,31). So we checked the expression levels of p-Akt and p-Smad2/3 at wound edge from Ppm1a-null and control mice by Western blot.…”
Section: Deletion Of Ppm1a Led To Delayed Re-epithelialization Duringmentioning
confidence: 99%
“…This result support our assumption regarding the indirect inhibition of PI3K by PRKCA, since, if PRKCA directly phosphorylates PI3K leading to its inhibition, the phosphatases inhibition would result in even greater PI3K inhibition, and this was not the case. An opposite regulation of PI3K by phosphatases was found in 3T3-L1 adipocytes in which overexpression of PP2Ca resulted in direct activation of PI3K by dephosphorylating the inhibitory site Ser608 in PI3K regulatory subunit -p85 (Yoshizaki et al 2004). The fact that PI3K has many phosphorylation sites which are activatory or inhibitory (Yoshizaki et al 2004, together with the established existence of variety of modulators, targeting and regulatory subunits that function as complexes with phosphatases and regulate their specific activity (Cohen 2002), points to the possibility that different phosphatases have specific sites for dephosphorylation on PI3K.…”
Section: Regulation Of Pi3k In Spermmentioning
confidence: 99%
“…An opposite regulation of PI3K by phosphatases was found in 3T3-L1 adipocytes in which overexpression of PP2Ca resulted in direct activation of PI3K by dephosphorylating the inhibitory site Ser608 in PI3K regulatory subunit -p85 (Yoshizaki et al 2004). The fact that PI3K has many phosphorylation sites which are activatory or inhibitory (Yoshizaki et al 2004, together with the established existence of variety of modulators, targeting and regulatory subunits that function as complexes with phosphatases and regulate their specific activity (Cohen 2002), points to the possibility that different phosphatases have specific sites for dephosphorylation on PI3K. Therefore, we assume that PPP1 dephosphorylates PI3K on 'positive'/stimulatory-phospho-site, leading to PI3K inhibition.…”
Section: Regulation Of Pi3k In Spermmentioning
confidence: 99%